(untitled) (Филолошки студии, 2019)
Basically, social psychology is centered around the only question: the relationship between the individual and society. Is the society just a sum of individuals or are individuals just elements of the society? We can approach the essence of this question by studying the work of some authors who could be regarded as predecessors of social psychology. First we have Wilhelm Wundt and Émile Durkheim as historically acknowledged forefathers of social psychology’s both parent disciplines, namely psychology and sociology. Then we have George Herbert Mead, whose life was dedicated to the integration of these two disciplines and who could therefore be regarded as the first social psychologist. The article presents some basic ideas of these authors concerning the question about the relationship between the individual and the society.